Dr. Hugo Donovan — Deep Plane Facelift — Brasília - Donovan, Hugo (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Hugo Donovan, practicing in Brasília, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003179; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil; brasília